Urban Farming sebagai Solusi Kemandirian Pangan dan Lapangan Kerja Baru di Bangka Belitung: (Studi Kasus Kota Pangkalpinang) - Aprilia Martika; Amelia Sari; Disti Macela Putri; Misbahul Munir (Universitas 45 Surabaya, 2025)
This study, titled “Urban Agriculture as a Solution for Food Independence and New Job Opportunities in Bangka Belitung: A Case Study of Pangkalpinang City,” investigates the application of urban agriculture as an adaptive strategy to address food insecurity and unemployment in urban areas with limited agricultural land. Pangkalpinang City faces increasing challenges related to urbanization, including declining agricultural land, high dependence on external food supplies, and limited employment opportunities for residents. The purpose of this study is to analyze how urban agriculture contributes to food independence, the creation of new job opportunities, and community participation in sustainable urban agriculture. Using a qualitative case study approach, data were collected through participant observation, in-depth interviews, and documentation studies, and analyzed thematically and through a SWOT analysis to identify internal and external factors influencing urban agriculture development. The study findings indicate that urban agriculture in Parit Lalang, Pangkalpinang, is mostly carried out in small home gardens and vacant land using hydroponic and traditional methods, with the main participants being productive-age residents and housewives. This practice has increased household food availability, reduced living costs, and generated additional income, thus enhancing local economic resilience. However, several challenges remain, such as limited technical skills, financial constraints, and inconsistent government support. The study concluded that strengthening training programs, improving access to finance, and developing pilot projects